NILAI PELANGGAN DITINJAU DARI KELAS MEREK DAN CITRA MEREK PADA PRODUK KOSMETIK - Rahayu Mardikaningsih; Samsul Arifin; Arif Rachman Putra; Misbachul Munir; Tri Seno Anjanarko (Jurnal Ilmiah Satyagraha, 2023)
Marketing Management is not only faced with increasingly strongbusiness competition but also changes in consumer behavior. The development oftechnology and changes in lifestyle cause consumers to have dynamic behavior.Customer value is one of the consumer behavior that can change the direction of thecompany's marketing. All factors considered capable of influencing customer valuewere studied such as brand class and brand image. This research was conducted todetermine customer value in terms of brand class and brand image. The study wasconducted on 90 users of SKII brand facial care products. The research sample wasobtained by purposive sampling which will then fill in the questionnaire which is thesource of the data for this research. The data is processed by regression technique.The results of the study show that brand class influences the formation of customervalue to consumers. The results showed that the brand class affects the formation ofcustomer value to consumers. In addition, this study also shows that customer valuecan be developed by developing a brand image. Brand class together with brandimage have been proven to build customer value to consumers.